THE STATE OF INCLUSION OF HUMAN RIGHTS IN EFL SECONDARY SCHOOL TEXTBOOKS IN PALESTINE - Khalil Abdullah Aburezeq (INTERNATIONAL JOURNAL ON LANGUAGE, RESEARCH AND EDUCATION STUDIES, 2019)
AbstractHuman rights topic is one of the core issues to the peoples of this planet nowadays. It is a substantive issue even for school students to learn about. Therefore, this study aimed first to prepare a list of human rights for educational purposes and second to examine the existence of human rights in EFL secondary school textbooks in Palestine. The study also sought to show the distribution of human rights and their domains in the textbooks. To maintain the study objective, the researcher followed the analytical descriptive approach to investigate the presence of human rights in four EFL textbooks. The study reached a list of human rights included (29) human rights which are classified under five domains: civil rights, social rights, economic rights, cultural rights, political rights. In the light of the new list, the researcher investigated the presence of human rights in the books and found that the most frequented right is ‘the right to education’, the civil human rights are the top in the textbooks representing a percentage of (46.7%), while the political rights were the lowest representing (4%). According to the study scale, the study found that the overall human right inclusion in the textbooks is very high.KeywordsHuman Rights, EFL, School Textbooks